Imaging focal and interstitial fibrosis with cardiovascular magnetic resonance in athletes with left ventricular hypertrophy: implications for sporting participation - Waterhouse, D. F.; Ismail, T. F.; Prasad, S K.; Wilson, M. G.; O'Hanlon, R. (British Journal of Sports Medicine, 2012)
Long-term high-intensity physical activity is associated with morphological changes, termed as the `athlete's heart`. The differentiation of physiological cardiac adaptive changes in response to high-level exercise from pathological changes consistent with an inherited cardiomyopathy is imperative. Cardiovascular magnetic resonance (CMR) imaging allows definition of abnormal processes occurring at the tissue level, including, importantly, myocardial fibrosis. It is therefore vital in accurately making this differentiation. In this review, we will review the role of CMR imaging of fibrosis, and detail CMR characterisation of myocardial fibrosis in various cardiomyopathies, and the implications of fibrosis. Additionally, we will outline advances in imaging fibrosis, in particular T1 mapping. Finally we will address the role of CMR in pre-participation screening.